FACTORS AFFECTING THE QUALITY OF LIFE OF THE ELDERLY IN KO CHAN SUBDISTRICT MUNICIPALITY, KO CHAN DISTRICT,CHONBURI PROVINCE, THAILAND - ทุมาโต, วิชุดา; Chotpittayanon, Natnicha (Journal of MCU Phetchaburi Review, 2026)
The objectives of this research were: (1) to examine the level of quality of life of elderly people living in Ko Chan Subdistrict Municipality, Ko Chan District, Chonburi Province; and (2) to investigate the factors affecting the quality of life of the elderly in the same area. This study employed a quantitative research approach. The sample consisted of 230 elderly individuals aged 60 years and over who had continuously resided in Ko Chan Subdistrict Municipality for at least one year. The research instrument was a questionnaire. Data were analyzed using a statistical software program. Descriptive statistics, including frequency, percentage, mean, and standard deviation, were used to analyze general data, while inferential statistics consisted of t-test, F-test, and Pearson’s product–moment correlation coefficient. The research findings revealed that: (1) the overall quality of life of the elderly in Ko Chan Subdistrict Municipality, Chonburi Province, was at a high level in terms of health, environment, social aspects, economic aspects, and education. Additionally, information access, life security, and emotional aspects were also found to be at a high level overall; and (2) the factors affecting the quality of life of the elderly, including policies promoting health-related activities, social activity promotion policies, occupational promotion policies, and educational promotion policies, were at a high level overall.